EVALUASI EFEKTIVITAS PROGRAM PENDIDIKAN PROFESI GURU (PPG) DALAM MENINGKATKAN KOMPETENSI PROFESIONAL GURU MI - Ridwanudin, Dindin; Takiddin, Takiddin (Elementar : Jurnal Pendidikan Dasar, 2025)
This study evaluates the effectiveness of the Teacher Professional Education (PPG) program in improving teachers’ professional competence, focusing on pedagogical, professional, social, and personality aspects. The research employed a quantitative approach using an evaluative survey design. A total of 250 teachers participating in the 2024 PPG program in the Greater Jakarta area were selected through stratified random sampling. Data were collected using a closed-ended questionnaire with a 5-point Likert scale, which demonstrated strong validity and reliability (Cronbach’s alpha = 0.89). The results show that the PPG program contributed significantly to teachers’ competence development. Pedagogical competence experienced the highest improvement (87%), followed by professional competence (82%), social competence (78%), and personality competence (74%). In addition, 71% of respondents reported that the instructional methods implemented in the PPG program were highly relevant to classroom practice, while 68% indicated increased confidence in classroom management after completing the program. Overall, the findings confirm that the PPG program has a positive impact on teachers’ professional development. However, challenges remain in curriculum implementation and post-program mentoring. These results suggest that PPG should function not only as a certification program but also as a strategic instrument for improving the quality of teaching and learning. Strengthening curriculum design, mentoring systems, and collaboration between LPTKs and partner schools is therefore essential for sustainable teacher professional development.Keywords: Teacher Professional Education, Program Evaluation, Teacher Competence, Professionalism